Biological rationale for patient-specific treatment of breast cancer. Analysis of new data for breast cancer - R. M. Paltuev (ABV-press, 2020)
Breast cancer is the most common malignancy in females. More than 1.7 million of cases are detected annually worldwide. The incidence of breast cancer in Russia has increased by 64 % over the last 20 years. There was a 1.43-fold increase in the prevalence of breast cancer (from 297 to 457cases per 100,000) between 2005 and 2017. A total of59,538 new cases were registered in the Russian Federation in 2012. In Russia, breast cancer is the most common malignancy among women aged 40-85years and the second most common cancer among women aged 15-39 (after cervical cancer). The disease is primarily detected in women aged between 40 and 54 years (29.5 %). More than 66,000 of new cases of breast cancer are registered in the Russian Federation annually. In 2017, there were 70,293 new cases of breast cancer; of them, 49,134 patients (69.9 %) hade stage I-II breast cancer. There was a 0.02 % increase in the proportion of new cases of stage I-II breast cancer in 2016-2017. For this reason, it is important to study in depth the markers of breast cancer used in everyday practice in order to personalize the treatment of patients with breast cancer.